THE EFFECT OF SENTENCE COMBINING TECHNIQUE ON STUDENTS’ ACHIEVEMENT IN WRITING RECOUNT TEXT - Desy Mita Rahmani; Sumarsih (Universitas Negeri Medan, 2017)
This is an attempt to discover the effect of applying Sentence Combining Technique on Students’ Achievement in Writing Recount Text. It was conducted by using experimental research. The population of this research was the eighth (VIII) grade students of SMP Budi Satrya which consists of five parallel classes with the total number of sampling through lottery technique. The result was class VIII-1 consisted of 30 students became the experimental group and class VIII-3 consisted of 30 students became the control group. The experimental group was taught by using Sentence Combining Technique while the control group was taught by using Picture Word Inductive Model. The instrument for collecting the data was writing test. The data were analyzed by using t-test formula. The result shows that the value of t-observed (2.75) is higher than the value of t-table (2.004) ( α = 0.05 ) with the degree of freedom (df) = 58. It means that there is a significant effect of applying Sentence Combining Technique on the students’ achievement in writing Recount texts. So, the alternative hypothesis (Ha) is accepted.